Enhanced Drug Carriage Efficiency of Curcumin-Loaded PLGA Nanoparticles in Combating Diabetic Nephropathy via Mitigation of Renal Apoptosis - Asmita Samadder; Banani Bhattacharjee; Sudatta Dey; Arnob Chakrovorty; Rishita Dey; Priyanka Sow; Debojyoti Tarafdar; Maharaj Biswas; Sisir Nandi (Korean Pharmacopuncture Institute, 2024)
Background: Diabetic nephropathy (DN) is one of the major complications of chronic hyperglycaemia affecting normal kidney functioning. The ayurvedic medicine curcumin (CUR) is pharmaceutically accepted for its vast biological effects.Objectives: The Curcuma-derived diferuloylmethane compound CUR, loaded on Poly (lactide-co-glycolic) acid (PLGA) nanoparticles was utilized to combat DN-induced renal apoptosis by selectively targeting and modulating Bcl2.Methods: Upon in silico molecular docking and screening study CUR was selected as the core phytocompound for nanoparticle formulation. PLGA-nano-encapsulated-curcumin (NCUR) were synthesized following standard solvent displacement method. The NCUR were characterized for shape, size and other physico-chemical properties by Atomic Force Microscopy (AFM), Dynamic Light Scattering (DLS) and Fourier-Transform Infrared (FTIR) Spectroscopy studies. For in vivo validation of nephro-protective effects, Mus musculus were pre-treated with CUR at a dose of 50 mg/kg b.w. and NCUR at a dose of 25 mg/kg b.w. (dose 1), 12.5 mg/kg b.w (dose 2) followed by alloxan administration (100 mg/kg b.w) and serum glucose levels, histopathology and immunofluorescence study were conducted.Results: The in silico study revealed a strong affinity of CUR towards Bcl2 (dock score -10.94 Kcal/mol). The synthesized NCUR were of even shape, devoid of cracks and holes with mean size of ~80 nm having -7.53 mV zeta potential. Dose 1 efficiently improved serum glucose levels, tissue-specific expression of Bcl2 and reduced glomerular space and glomerular sclerosis in comparison to hyperglycaemic group.Conclusion: This study essentially validates the potential of NCUR to inhibit DN by reducing blood glucose level and mitigating glomerular apoptosis by selectively promoting Bcl2 protein expression in kidney tissue.